Tìm x , biết :
a) (5x + 1)2 - (5x + 3)(5x - 3) = 30
b) (x + 3)2 + (x - 2)(x + 2) - 2(x - 1)2 = 7
tìm x biết
a) 5x(2x-7)+2x(8-5x)=5
b)(3x-5)(7-5x)-(5x+2)(2-3x)=4
c)5(2x-3)^2-5(x+1)^2-15(x+4)(x-4)=-10
d) 5x(x-3)(x+3)-(2x-3)^2 -5(x+2)^3+34x(x+2)=1
a)
<=> 10x - 35 + 16x - 10 = 5
<=> 10x + 16x = 5 + 35 + 10
<=> 26x = 50
<=> x = 50/26 = 25/13
1. Tìm x, biết:
a, (x-2)^2-(x+3)^2-4(x+1)=5
b, (2x-3)(2x+3)-(x-1)^2-3x(x-5)=-44
c. (5x+1)^2-(5x+3)(5x-3)=30
d. (x+3)^2+(x-2)(x+2)-2(x-2)^2=7
a, \(\left(x-2\right)^2-\left(x+3\right)^2-4\left(x+1\right)=5\)
\(\Leftrightarrow x^2-4x+4-\left(x^2+6x+9\right)-4x-4=5\)
\(\Leftrightarrow x^2-4x+4-x^2-6x-9-4x-4=5\)
\(\Leftrightarrow-14x-9=5\)
\(\Leftrightarrow-14x=14\)
\(\Leftrightarrow x=-1\)
Vậy....
b, \(\left(2x-3\right)\left(2x+3\right)-\left(x-1\right)^2-3x\left(x-5\right)=-44\)
\(\Leftrightarrow\left(2x\right)^2-3^2-\left(x^2-2x+1\right)-3x^2+15x=-44\)
\(\Leftrightarrow4x^2-9-x^2+2x-1-3x^2+15x=-44\)
\(\Leftrightarrow-10+17x=-44\)
\(\Leftrightarrow17x=-34\)
\(\Leftrightarrow x=-2\)
Vậy....
c, \(\left(5x+1\right)^2-\left(5x+3\right)\left(5x-3\right)=30\)
\(\Leftrightarrow\left(5x\right)^2+10x+1-\left[\left(5x\right)^2-3^2\right]=30\)
\(\Leftrightarrow\left(5x\right)^2+10x+1-\left(5x\right)^2+9=30\)
\(\Leftrightarrow10x+10=30\)
\(\Leftrightarrow10x=20\)
\(\Leftrightarrow x=2\)
Vậy....
d, \(\left(x+3\right)^2+\left(x-2\right)\left(x+2\right)-2\left(x-2\right)^2=7\)
\(\Leftrightarrow x^2+6x+9+x^2-4-2\left(x^2-4x+4\right)=7\)
\(\Leftrightarrow2x^2+6x+5-2x^2+8x-8=7\)
\(\Leftrightarrow14x-3=7\)
\(\Leftrightarrow14x=10\)
\(\Leftrightarrow x=\frac{10}{14}=\frac{5}{7}\)
Vậy...
bn Nhật Hạ lm đúng r đấy
tìm x biết a (x-2)^2+(x+3)^2-4(x+1)=5
b (2x-3)(2x+3)-(x-1)^2-3x(x-5)=-44
c (5x+1)^2-(5x+3)(5x-3)=30
d (x+3)^2+(x-2)(x+2)-2(x-1)^2=7
bài 1 tìm x biết rằng
a, [ 2x - 3 ] mũ 2 - [2x + 1] mũ 2 = -3
b, [5x - 1] mũ 2 - [5x + 4] [5x - 4] = 7
c, [ x- 5] mũ 2 + [x-3][x+3] - 2[x + 1] mũ 2 =0
a, ( 2x - 3 )2- (2x + 1)2 = -3
4x2-12x+9-4x2+4x-1=-3
-8x-1=-3
-8x=-2
x=\(\frac{1}{4}\)
b, (5x - 1) 2 - (5x + 4)(5x - 4) = 7
25x2-10x+1-25x2+16=7
-10x+17=7
-10x=-10
x=1
c, ( x- 5)2 + (x-3)(x+3) - 2(x + 1)2=0
x2-10x+25+x2-9-2x2-4x-2=0
-14x+14=0
-14(x-1)=0
=>x-1=0
x=1
a) \(\left(2x-3\right)^2-\left(2x+1\right)^2=-3\)
\(\Leftrightarrow4x^2-12x+9-4x^2-4x-1=-3\)
\(\Leftrightarrow-16x+8=-3\)
\(\Leftrightarrow-16x=-11\)
\(\Leftrightarrow x=\frac{11}{16}\)
b)\(\left(5x-1\right)^2-\left(5x+4\right)\left(5x-4\right)=7\)
\(\Leftrightarrow25x^2-10x+1-25x^2+16=7\)
\(\Leftrightarrow-10x+17=7\)
\(\Leftrightarrow-10x=-10\)
\(\Leftrightarrow x=1\)
c)\(\left(x-5\right)^2+\left(x-3\right)\left(x+3\right)-2\left(x+1\right)^2=0\)
\(\Leftrightarrow x^2-10x+25+x^2-9-2\left(x^2+2x+1\right)=0\)
\(\Leftrightarrow2x^2-10x-16-2x^2-4x-2=0\)
\(\Leftrightarrow-14x-18=0\)
\(\Leftrightarrow-14x=18\)
\(\Leftrightarrow x=-\frac{9}{7}\)
#H
Bài 2 : Tìm x , biết
a) ( 3x -1 ) (2x+7) - ( x +1) (6x-5 ) = 16
b) ( 10x +9 )x - ( 5x -1 ) (2x+3 )= 8
c) ( 3x - 5 ) ( 7- 5x ) + ( 5x +2 )( 3x-2 ) -2 = 0
d) x(x + 1) ( x+6 ) - x3 = 5x
Tìm x biết a) (x^2-4x+5)_(x^2-2x+1)=3 lớp 7
b)(4x^3-5X^2+3x-1)+(3-5x+5x^2-4x^3)=2
c)(3x-2)-(5x+4)=(x-3)-(X+5)
a, \(-4x+5+2x-1=3\Leftrightarrow-2x=-1\Leftrightarrow x=\dfrac{1}{2}\)
b, \(-2x+2=2\Leftrightarrow x=0\)
c, \(-2x-6=-8\Leftrightarrow x=1\)
tìm x biết
a,(x-2)^2-(x+3)^2-4(x+1)=5
b, (2x-3)(2x+3)-(x-1)^2-3x(x-5)=-44
c, (5x+1)^2-(5x+3)(5x-3)=30
d,(x+3)^2+(x-2)(x+2)-2(x-1)^2=7
giúp mik vs mik cần gấp
1. Tìm x
a. (5x-7)(x-9)-(-x+3)(-5x+2)= 2x(x-4)-(x-1)(2x+3)
b. (x-3)(-x+10)+(x-8)(x+3)= (5x^2-1)(x+3)-5x^3-15x^2
ta có
a. (5x-7)(x-9)-(-x+3)(-5x+2)= 2x(x-4)-(x-1)(2x+3)
\(\Leftrightarrow5x^2-52x+63-\left(5x^2-17x+6\right)=2x^2-8x-\left(2x^2+x-3\right)\)
\(\Leftrightarrow-35x+57=-9x+3\Leftrightarrow26x=54\Leftrightarrow x=\frac{27}{13}\)
b. (x-3)(-x+10)+(x-8)(x+3)= (5x^2-1)(x+3)-5x^3-15x^2
\(\Leftrightarrow-x^2+13x-30+x^2-5x-24=5x^3+15x^2-x-3-5x^3-15x^2\)
\(\Leftrightarrow8x-54=-x-3\Leftrightarrow9x=51\Leftrightarrow x=\frac{17}{3}\)
Tìm x biết :
a) 3(5/3x-7)-2(1.5x+6)-(5-x)(x+4)=80+x^2
b) 4/5x^2(x/3-1/2)-(1/5x-2/3)(4x^2/3+1)=22/45x^2
`Answer:`
\(3\left(\frac{5}{3}x-7\right)-2\left(1.5x+6\right)-\left(5-x\right)\left(x+4\right)=80+x^2\)
\(\Leftrightarrow3\left(\frac{5x}{3}-7\right)-2\left(5x+6\right)-\left(5-x\right)\left(x+4\right)=80+x^2\)
\(\Leftrightarrow5x-21-10x-12-5x-20+x^2+4x=80+x^2\)
\(\Leftrightarrow5x-21-10x-12-5x-20+4x=80\)
\(\Leftrightarrow-6x-53=80\)
\(\Leftrightarrow-6x=133\)
\(\Leftrightarrow x=-\frac{133}{6}\)
\(\frac{4}{5}x^2\left(\frac{x}{3}-\frac{1}{2}\right)-\left(\frac{1}{5}x-\frac{2}{3}\right)\left(4\frac{x^2}{3}+1\right)=\frac{22}{45}x^2\)
\(\Leftrightarrow36x^2\left(\frac{x}{3}-\frac{1}{2}\right)-45\left(\frac{x}{5}-\frac{2}{3}\right)\left(\frac{4x^2}{3}+1\right)=22x^2\)
\(\Leftrightarrow12x^3-18x^2-12x^3-9x+40x^2+30=22x^2\)
\(\Leftrightarrow22x^2-9x+30=22x^2\)
\(\Leftrightarrow-9x+30=0\)
\(\Leftrightarrow-9x=-30\)
\(\Leftrightarrow x=\frac{10}{3}\)